STATISTICAL ANALYSIS OF DILAPIDATED AND DANGEROUS BUILDINGS IN INDIA: OPTIMIZING TDR ALLOCATION FOR URBAN REDEVELOPMENT - Patil, Shubhada S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper presents a comprehensive statistical analysis of dilapidated and dangerous buildings across urban wards in India, focusing on optimising the allocation of Transferable Development Rights (TDR) for effective urban redevelopment. By integrating empirical data on building conditions, urban density, and redevelopment patterns, the study develops a dynamic framework that applies advanced statistical models to evaluate the efficiency of TDR allocations in high-risk zones. The research addresses critical issues of liquidity constraints, TDR hoarding, and inefficient redevelopment processes, proposing a refined mechanism for optimising TDR distribution through data-driven strategies. The proposed model balances redevelopment incentives with environmental and infrastructural sustainability by incorporating real-time market dynamics and environmental cost factors into TDR pricing. This study also includes case studies on slum redevelopment and real estate liquidity, offering actionable insights for policymakers to deploy TDR exchanges to accelerate urban regeneration. The findings contribute to the advancement of sustainable urban growth by offering a novel approach to resolving redevelopment inefficiencies while maintaining ecological balance.